Unique nucleotide difference of two putative Ty1/copia-like long terminal repeat retrotransposons of abaca (Musa textilis Nee) - Yllano, Orlex B.; Lalusin, Anton; Castro, Sheryl D.; Laurena, Antonio C.; Tecson-Mendoza, Evelyn Mae (2011)
Retrotransposons or transposons through RNA intermediates are ubiquitous mobile genetic elements that can amplify themselves in the eukaryotic genomes. It harbors regulatory signals that are responsible for chromosomal rearrangements, fragmental gene movements, alteration of gene expression, and genome evolution. In this study, the putative abaca retrotransposons were cloned, verified, sequenced, and caracterized. The resulting PCR products were cloned using degenerate primers. Restriction digestion of the purified recombinant plasmid using EcoRI revealed a distinct band (~950 bases). Sequence analysis revealed 868-base perfect alignment insert. Comparing and aligning the two nucleotide substitution at 779 from T in Retroclone1 to C in Retroclone2. Using sequence alignment and phylogenetic analysis, the cloned putative retrotransposons of M. textilis grouped with Ty1-copia retrotransposon of M. ABB, M. AAB, and M. acuminata. High homology to known retrotransposon protein of Oryza sativa, putative polyprotein of Oryza australiensis, gag-pol of Zea mays, integrase core domain of O. sativa and reverse transcriptase was noted using Blastx. This result supports the generalized structure of retrotransposon which is characterized with gag, pol and env domains in between the long terminal ends (LTRs). To our knowledge, this is the first report on the cloning and sequence analysis of putative abaca retrotransposon. These results provide insight in understanding the genome composition of the Philippines indigenous fiber crop - abaca.
Keywords: Abaca